A new species of the genus Terebellides (Polychaeta, Trichobranchidae) from the Iranian coast - Parapar, Julio; Moreira, Juan; Gil, João; Martin, Daniel (Zootaxa, 2016)
Based on specimens collected during several sampling programmes along the Iranian coast, Persian Gulf, a new species of the genus Terebellides (Polychaeta, Trichobranchidae) is herein described as Terebellides persiae spec. nov. The new species is primarily characterised by the presence of a large dorsal thoracic hump in larger specimens and ciliated papillae on the branchial lamellae. The new species is compared with other taxa belonging to Terebellides described or reported with any of both characters. SEM and micro-CT have been used to study T. persiae spec. nov. and provide several new details on external characters and internal organs, respectively. A key for the identification of the species of Terebellides with dorsal hump is provided.